Article II, the Vacancies Act and the Appointment of “Acting” Executive Branch Officials - Brannon P. Denning (Washington University Law Quarterly, 1998)
This Article looks at both the Vacancies Act, as well as the provisions with which the Administration countered, in the context of both the Lee nomination and one other case (largely ignored by the press) involving Duke law professor Walter E. Dellinger's service as acting Solicitor General from July 1996 until August 1997. Contrary to Administration claims, I conclude that the Vacancies Act does apply to Justice Department officials, and that the statute cited by the Administration allegedly superseding the Vacancies Act, if not read in harmony with that Act, unconstitutionally allows the President and the Attorney General to circumvent the Senate's constitutional advice and consent role set forth in Article II.
Keywords: Executive power; Executive departments (Government); Government officials; Department of Justice Act; Presidential Transition Effectiveness Act; United States Constitution